Reimagining Human Rights : Religion and the Common Good - O'Neill, William R. (Book collections on Project MUSE., 2021)
"Jeremy Bentham described the idea of human rights as "rhetorical nonsense." In this book, which is proposed for the Moral Traditions series, William O'Neill shows that the rhetorical aspect of human rights is in fact crucial. He does so by examining how victims and their advocates embrace the rhetoric of human rights to tell their stories. It is a history of human rights "from below," showing what victims of atrocity and advocates do with rights. Using a group of American writings, including Desmond Tutu's on the Truth and Reconciliation Commission, O'Neill reconciles the false dichotomy between the individualistic perspective of the human rights theory of Kant, Rousseau, and Rawls and the communitarian approach of Burke, Bentham, and Alasdair Macintyre. He shows that the testimony of the victims of atrocities leads us to a new conception of the common good, based both on abstract theories of individual human rights and the circumstances and history of particular societies. The book then applies this new approach to three areas: race and mass incarceration in the U.S, the politics of immigration and refugee policy, and our duties to the next generation and the non-human world"--